2023
DOI: 10.1021/acsinfecdis.3c00014
|View full text |Cite
|
Sign up to set email alerts
|

Alanyl-Glutamine (Ala-Gln) Ameliorates Dextran Sulfate Sodium (DSS)-Induced Acute Colitis by Regulating the Gut Microbiota, PI3K-Akt/NF-κB/STAT3 Signaling, and Associated Pulmonary Injury

Abstract: The aim of this study was to investigate the protective effect of alanyl-glutamine (Ala-Gln) on acute colitis complicated by pulmonary injury induced by dextran sulfate sodium (DSS) in C57BL/6 mice. The results showed that Ala-Gln intervention alleviated weight loss, the disease activity index (DAI), colon shortening, and pathological injury and regulated the absolute number of CD4 + T-cell subsets in mesenteric lymph nodes (MLNs). In addition, Ala-Gln intervention significantly ameliorated the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…These findings suggest that Clostridia vadinBB60 group may have anti-inflammatory properties. Consistent with this notion, two studies have reported that Clostridia vadinBB60 group is protective in IBD 42,43 .…”
Section: Discussionmentioning
confidence: 57%
“…These findings suggest that Clostridia vadinBB60 group may have anti-inflammatory properties. Consistent with this notion, two studies have reported that Clostridia vadinBB60 group is protective in IBD 42,43 .…”
Section: Discussionmentioning
confidence: 57%
“…Currently, a greater diversity and richness in gut bacteria are considered advantageous, helping animals navigate various environmental challenges. Gln and glutamine peptides have been reported to preserve intestinal structure and function, in addition to enhancing growth performance, by modulating gut microbiota [34]. In this study, microbial diversity, richness, and community abundance experienced a significant upsurge when GCFF replaced 15% and 30% of SBM (Figure 2).…”
Section: Discussionmentioning
confidence: 74%
“…AESc upregulated the abundance of beneficial Alcaligenaceae (Collins et al, 2014), Coriobacteriaceae (Sun et al, 2023), Ruminococcaceae (Keshteli et al, 2022), Lachnospiraceae (Herp et al, 2019), [Paraprevotellaceae], Mucispirillum (Herp et al, 2019), Adlercreutzia (Chen et al, 2019), Allobaculum (van Muijlwijk et al, 2021, [Ruminococcus] (Lee et al, 2017), and [Prevotella] (Iljazovic et al, 2021) and downregulated the abundance of pathogenic Turicibacteraceae (Tong et al, 2021), Enterobacteriaceae (Hu et al, 2022), Proteus (Zhang et al, 2021), Turicibacter (Meng et al, 2019), Coprococcus (Yang et al, 2023), Shigella (Dekker and Frank, 2015), and Prevotella (Sharma et al, 2022). However, the modulating effects on Desulfovibrionaceae (Liu et al, 2023), Deferribacteraceae (Berry et al, 2012), Helicobacteraceae Tong et al, 2021), Verrucomicrobiaceae (Tong et al, 2021), Bacteroidaceae (Peng et al, 2019), Lactobacillaceae (Ma L. et al, 2022), Prevotellaceae (Liu et al, 2020), Oscillospira (Chen et al, 2021), Akkermansia (Qu et al, 2021), Bacteroides (Shao et al, 2021), and Lactobacillus (Jia et al, 2022) were inconsistent with the literature reports. We hypothesized that AESc regulates the UC intestinal flora selectively.…”
Section: Discussionmentioning
confidence: 99%